Intraoperative clonidine for prevention of postoperative agitation in children anaesthetised with sevoflurane (PREVENT AGITATION): a randomised, placebo-controlled, double-blind trial. (January 2018) - Ydemann, Mogens; Nielsen, Bettina Nygaard; Henneberg, Steen; Jakobsen, Janus Christian; Wetterslev, Jørn; Lauritsen, Torsten; Steen, Nick; Edstrøm, Birgitte; Afshari, Arash; ,
Summary: Background: Postoperative agitation is a frequent and stressful condition for a child, their family, and their health-care providers, and prevention would be of benefit. We aimed to assess the effects of intravenous clonidine administered intraoperatively on the incidence of postoperative agitation, pain, and adverse events. Methods: We did this randomised, placebo-controlled, double-blind trial (PREVENT AGITATION) at one tertiary-level hospital and two urban-district hospitals in Denmark. Children aged 1–5 years, with an American Society of Anesthesiologists physical classification score of 1–2, who were scheduled for anaesthesia with sevoflurane and fentanyl were randomly assigned (1:1) in blocks of ten by computer-generated centralised randomisation, stratified by age (<2 years or ≥2 years) and site, to receive either intravenous clonidine 3 μg/kg or an equal quantity of isotonic saline in identical vials, administered around 20 min before the completion of surgery. Data were collected from the postoperative care unit (24 h) and at follow-up (30 days). Our primary outcome was the proportion of patients with one or more episodes of postoperative agitation, measured every 15 min in the postoperative care unit (POCU) with the four-point Watcha scale (ie, Watcha >2). We analysed by intention to treat. The trial is registered with ClinicalTrials.gov (number NCT02361476 ). Findings: Between January and December, 2015, of the 379 eligible children, we randomly assigned 191 to receive clonidine treatment and 188 to receive placebo; 75 were girls (20%). Nine were excluded from the primary outcome analysis because of missing data points. 46 (25%) of 187 clonidine participants compared with 86 (47%) of 183 placebo participants had one or more episodes of postoperative agitation (Watcha score >2; relative risk 0·56, 95% CI 0·43–0·73; p<0·0001). 30 (20%) of 150 boys in the clonidine group were agitated compared with 69 (47%) of 147 boys in the placebo group (0·43, 0·30–0·61; p<0·0001). The observed effect was not significant in girls. Incidence of adverse events was similar in the clonidine and placebo groups. Interpretation: On the basis of our results, clonidine might be used to safely prevent postoperative agitation in boys anaesthetised with sevoflurane. Funding: Danish Society of Anaesthesia and Intensive Care.